Mobile Apps Pendidikan Islam SPM Sirah dan Tamadun (Khulafa’ Ar-Rasyidin) - Mohd Jamil Aris, Muhammad Nazmi; Abd Aziz, Fadzillah (Journal of Computing Technologies and Creative Content, 2021)
Pendidikan Islam is one of the subjects which become compulsory for Muslim students taking Sijil Pelajaran Malaysia (SPM) examination. Pendidikan Islam is divided into sections including al-Quran, Hadith, Akidah, Fiqh, Akhlak and Sirrah. Khulafa ’Ar-Rasyidin is one of the topics in Sirrah that describes the history and events in the Islamic era after the demise of prophet Muhammad (pbuh). Technological advancement and various applications, such as entertainment, will now contribute to a lack of interest in education for students. As an alternative, the research practically developed a 2D animation as an edutainment to improve the quality of learning for students, especially SPM students, as well as to promote a mobile application for education. Islamic history is very important to students in connecting the past with the present era. The design and prototypes development employed in this study are based on waterfall model. This application was evaluated by 30 respondents, consisting of teachers and students, using a pilot test to find out its acceptance as an edutainment material. The overall evaluation of this apps had a positive impact on teachers and students as they enjoyed learning Pendidikan Islam through Mobile Application.